Combinatorial drug repurposing of Valproic acid and Zebularine regulates Krüppel-like factor 4 and β-catenin expression in colon cancer cells - Jeyalakshmi Kandhavelu; Kumar Subramanian; Natanya Moodley; Kasim S. Abass; Chandrabose Sureka; Meenakshisundaram Kandhavelu; Paul Ruff; Clement Penny (PLoS ONE, 2026)
Colorectal cancer is the predominant and recurring cancer leading to the second largest cause of mortality, globally. Abnormal regulation of oncogenes and deactivation of tumor suppressor genes over an extended period were key mechanisms underlying colon tumorigenesis. As a result, an effective drug targeting these genes should be explored to combat this disease. We aim to explore the effects of Valproic acid (VPA), a histone deacetylase inhibitor (HDACi), and Zebularine (ZEB), DNA methyltransferase inhibitor, on the expression of the Krüppel-like factor 4 (KLF4) and CTNNB1 (β-catenin) in an early-stage colon cells (SW480 cells) and a late-stage colon cell (DLD-1 cells). Using several in-vitro assays including cell viability, proliferation assay, single cell imaging and analysis and molecular assays including qPCR, protein expression analysis, we have assessed the anticancer properties of both drugs, VPA and ZEB. The synergistic effect of VPA and ZEB could effectively inhibit the proliferation of colon cells than their independent doses. The gene expression profile revealed 2-fold increase in the expression of KLF4 in SW480 cells, with increase to about 22-fold in DLD-1 cells. Notably, CTNNB1 was downregulated than KLF4 in a dose dependent manner, potentially leading to antitumorigenic and anti-proliferative properties of the combinatorial drug. Cellular localization of KLF4 and CTNNB1 protein expression in cytoplasm and nucleus with morphological changes of the cancer cells revealed the onset of programmed cell death. qPCR analysis also showed the downregulation of KLF4 and CTNNB1 upon synergistic activity of ZEB and VPA treated colon cancer cells. Microscopic analysis confirmed the upregulation of KLF4 in ZEB treatment cells leading to DNA methylation. Finally, single cell image analysis has shown the reduced expression of both KLF4 and CTNNB1. Overall, the analysis confirmed that synergistic effect of ZEB and VPA served as a potential anti-colon cancer agent.